2008
DOI: 10.1162/jocn.2008.20157
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Auditory-evoked Potentials in Musicians Reflects an Influence of Expertise but not Selective Attention

Abstract: Instrumental tones and, in some instances, simple sine-wave tones were shown to evoke stronger auditory-evoked responses in musicians compared to nonmusicians. This effect was taken as an example for plasticity in the auditory cortex elicited by training. To date, however, it is unknown whether an enlarged cortical representation for (instrumental) tones or increased neuronal activity provoked by focused attention in musicians accounts for the reported difference. In an attempt to systematically investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
107
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 48 publications
20
107
0
2
Order By: Relevance
“…While the role of attention with respect to musicians' perception remains debated (e.g., Baumann et al, 2008; Koelsch et al, 1999), research has shown that musicians differ from nonmusicians in the way that attention modulates electrophysiological indices of auditory perception Strait et al, 2012b). Thus, attentional differences between musicians and non-musicians may account for group differences in the detection of potentially less salient acoustic cues (Strait et al, 2010;Strait & Kraus, 2011b;Fujioka et al, 2006).…”
Section: Auditory Attention and Influence On Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the role of attention with respect to musicians' perception remains debated (e.g., Baumann et al, 2008; Koelsch et al, 1999), research has shown that musicians differ from nonmusicians in the way that attention modulates electrophysiological indices of auditory perception Strait et al, 2012b). Thus, attentional differences between musicians and non-musicians may account for group differences in the detection of potentially less salient acoustic cues (Strait et al, 2010;Strait & Kraus, 2011b;Fujioka et al, 2006).…”
Section: Auditory Attention and Influence On Perceptionmentioning
confidence: 99%
“…While the role of attention with respect to musicians' perception remains debated (e.g., Baumann et al, 2008;Koelsch et al, 1999), research has shown that musicians differ from nonmusicians in the way that attention modulates electrophysiological indices of auditory perception (e.g., Tervaniemi et al, 2005Tervaniemi et al, , 2009Seppänen et al, 2012; see also Marie et al, 2011). Compared to non-musicians, musicians show increased N2b component amplitudes for attended intensity, frequency and duration deviances in speech and musical sounds (Tervaniemi et al, 2009), and significant reductions in P3b amplitudes when attending to subtle pitch deviances .…”
Section: Musicianship Attention and Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, there is general agreement that musical training has a profound influence on N1/P2 responses during both active (Marie, Magne, et al, 2011;Shahin, Bosnyak, Trainor, & Roberts, 2003) and passive (Seppanen, Hamalainen, Pesonen, & Tervaniemi, 2012;Baumann, Meyer, & Jäncke, 2008) listening conditions. The effects of intense musical training on auditory processing have been well documented in various cross-sectional (Baumann et al, 2008;Meyer et al, 2006;Pantev et al, 1998; and longitudinal (Chobert, Francois, Velay, & Besson, 2012;Hyde et al, 2009;Moreno et al, 2009) studies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, methods such as functional magnetic resonance imaging (fMRI), electroencephalography (EEG), and magnetoencephalography (MEG) (e.g. Ohnishi et al, 2001;Baumann et al, 2008;Pantev et al, 1998) have been employed to study functional plasticity.…”
mentioning
confidence: 99%